2005
DOI: 10.1002/anie.200501467
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Chirality in a Hierarchical Supramolecular Self‐Assembled Structure with Pentagonal Symmetry

Abstract: Nested assembly: Chiral molecules of 5,6,11,12‐tetraphenylnaphthacene (rubrene) organize spontaneously into homochiral supramolecular architectures of increasing complexity. Adsorbed individual molecules self‐assemble enantioselectively into chiral pentagonal supermolecules, which act as building blocks for the formation of chiral supramolecular decagons (see STM images).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 26 publications
(12 reference statements)
6
89
2
1
Order By: Relevance
“…46 Scanning tunneling microscopy (STM) studies of rubrene on Au(111) carried out at 5 K demonstrated that the twisted conformation of the molecule and its chirality are retained upon physisorption and can be exploited to drive the assembly of exotic chiral hierarchical supramolecular structures. 47 STM investigations were carried out also on single-crystal surfaces in ambient air and revealed a herringbone-like motif similar to that found in the bulk. 48 In this paper, we investigate the adsorption and self-assembly properties of rubrene molecules on the O-Cu nanotemplate by in situ high-resolution STM in UHV.…”
Section: Introductionsupporting
confidence: 53%
“…46 Scanning tunneling microscopy (STM) studies of rubrene on Au(111) carried out at 5 K demonstrated that the twisted conformation of the molecule and its chirality are retained upon physisorption and can be exploited to drive the assembly of exotic chiral hierarchical supramolecular structures. 47 STM investigations were carried out also on single-crystal surfaces in ambient air and revealed a herringbone-like motif similar to that found in the bulk. 48 In this paper, we investigate the adsorption and self-assembly properties of rubrene molecules on the O-Cu nanotemplate by in situ high-resolution STM in UHV.…”
Section: Introductionsupporting
confidence: 53%
“…48 The STM images obtained on Cu(100) suggest that the tetracene backbone of the molecule lies parallel to the surface. To gain further insight into the molecules' conformation we analyzed series of apparent height profiles of the phenyl substituents of rubrene molecules adsorbed on Cu(100).…”
Section: Resultsmentioning
confidence: 99%
“…40 The excellent charge transport properties of rubrene have motivated several fundamental studies of rubrene single crystals, [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] thin films, [43][44][45][46][47] and self-assembled structures. 28,[48][49][50] Rubrene is a nonplanar and flexible molecule consisting of a tetracene backbone with two pairs of phenyl substituents symmetrically attached on either side of the backbone ( Figure 1). The intramolecular steric hindrance between the phenyl substituents results in a significant strain within the molecule, which can be released by either a twisting of the tetracene backbone as seen in the gas phase geometry (Figure 2, conformation A), or by an out-of-plane distortion of the phenyl substituents seen in the single crystal geometry (Figure 2, conformation B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar apolar intrinsically chiral molecule, the aromatic 5,6,11,12-tetraphenyltetracene (rubrene, Fig. 21), however, shows a remarkable hierarchical homochiral recognition [133]. The molecule is another example of a chiral structure due to steric overcrowding and the absence of a stereogenic center.…”
Section: Racemic Mixturesmentioning
confidence: 99%